Sister mother warrior : a novel [compact disc, unabridged] - Riley, Vanessa (HarperCollins, 2022)
When war breaks out on Saint Domingue, Marie-Claire and Gran Toya meet and, despite their differences, play pivotal roles in the revolution that will lead to full independence for Haiti and its people.